Classification of bleeding events: comparison of ECASS III (European Cooperative Acute Stroke Study) and the New Heidelberg bleeding classification - Neuberger, Ulf; Möhlenbruch, Markus Alfred; Herweh, Christian; Ulfert, Christian; Bendszus, Martin; Pfaff, Johannes (Stroke, 2017)
Intracranial hemorrhage (ICH) after acute ischemic stroke treatments represents a feared complication with possible prognostic implications. In recent years, ICHs were commonly classified according to the ECASS (European Cooperative Acute Stroke Study). To improve the clinical applicability and relevance, the new Heidelberg Bleeding Classification (HBC) has been proposed in 2015. Here, we compared the ECASS and HBC classification with regard to observed events and prognostic relevance.